Organizational Culture, Absorptive Capacity, Innovation Performace and Competitive Advantage: An Integrated Assessment in Indonesian Banking Industry - Adriansyah, Ahmad; Afiff, Adi Zakaria (UI Scholars Hub, 2015)
The positive impact of absorptive capacity (ACAP) on innovation and the positive impact of innovation on competitive advantage have been proven in different research contexts. However, current knowledge on organizational culture that affects ACAP, innovation and competitive advantage as a whole, remains unclear. This article proposes a model to examine how organizational culture (developmental culture and rational culture) affects ACAP, innovation and competitive advantage, directly and indirectly as well. Surveyed data (in Indonesian Banking Industry) shows that both of organizational culture have a direct impact on ACAP. Only developmental culture has a direct impact on innovation. There is no culture type affects competitive advantage directly. In this research, culture affects competitive advantage through ACAP and innovation.